2021
DOI: 10.14710/ijred.2021.36277
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Light Incidence Angle on Photoelectric Parameters of Solar Cells by Simulation

Abstract: It is crucial to examine the dependence of photoelectric parameters of solar cells on the light incidence angle. In the present study, two solar cell models have been developed using the Sentaurus Technology Computer-Aided Design software package. The light spectrum AM1.5 has been directed on the frontal surface of solar cells at different angles. It has been found that the angular coefficient of the photoelectric parameters of a solar cell with nanoparticles included, is two times more than that of a simple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…As θ is increased, J SC and η are gradually decreased (Figure e). Because the absorption intensity is decreased with the increase of incident angle, the J SC was reduced due to the lowered absorption intensity in the semiconductor layer, resulting in low exciton generation rate . Consequently, it reduces the total η following eq .…”
Section: Resultsmentioning
confidence: 99%
“…As θ is increased, J SC and η are gradually decreased (Figure e). Because the absorption intensity is decreased with the increase of incident angle, the J SC was reduced due to the lowered absorption intensity in the semiconductor layer, resulting in low exciton generation rate . Consequently, it reduces the total η following eq .…”
Section: Resultsmentioning
confidence: 99%
“…We thought the inputting of nanoparticles into n region of silicon solar cell give chance to use resonance phenomenon in addition to changing the light spectrum. In our previous scientific works, it was found that its efficiency is good when size of the nanoparticle is 15-20 nm [8], [9]. In figure 2, dependence of absorption coefficient of Au, Ag, Cu, Pt NISSCs and SSC on wavelength are shown.…”
Section: Resultsmentioning
confidence: 90%
“…Motion of carriers forms current. Basically, connection between carrier concentration and current density is expressed by "general continuity equations" which are shown in formula (7) and (8).…”
Section: Methodsmentioning
confidence: 99%
“…where 'K i ' is the temperature coefficient of 'Isc'; T: operating temperature (K); 'G': solar insolation representing a full-sunlight condition as the illumination of sunlight varies widely in intensity and spectrum [96]. Second, modelling the reverse saturation current 'I rs ' as follows:…”
Section: Simulation Of Solar Cells By Matlab/simulinkmentioning
confidence: 99%